Metagenomics - Basics, Methods and Applications 2020
DOI: 10.5772/intechopen.86302
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metagenomics to Chilean Aquaculture

Abstract: Aquaculture is a rapidly expanding food production sector, facing the challenge of growth both increasing its efficiency and reducing its negative impact on the environment. Metagenomics is an emerging tool in aquaculture that helps to understand the complex host (fish-shellfish)-microbiota-pathogen-environment relationship underlying disease outbreaks, monitoring the dynamics of microbial diversity in farmed animals subject to different environmental conditions or perturbations. As Chile takes an important sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 183 publications
0
8
0
Order By: Relevance
“…This interaction implies induction of gene expression and protein synthesis on both sides, and an infectious process may develop in the host, leading ultimately to death, if the host response or defense system fails to combat the pathogenic challenge [ 171 ]. However, a wider perspective on host-pathogen interactions may be undertaken [ 172 ], spanning these interactions to the associated microbial populations e.g., the host microbiome, known as the “holobiome” approach [ 173 ]. Indeed, it has been demonstrated that the microbiota may play a critical role in the immune response of organisms [ 174 ].…”
Section: Tools For the Study Of Host-pathogen Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…This interaction implies induction of gene expression and protein synthesis on both sides, and an infectious process may develop in the host, leading ultimately to death, if the host response or defense system fails to combat the pathogenic challenge [ 171 ]. However, a wider perspective on host-pathogen interactions may be undertaken [ 172 ], spanning these interactions to the associated microbial populations e.g., the host microbiome, known as the “holobiome” approach [ 173 ]. Indeed, it has been demonstrated that the microbiota may play a critical role in the immune response of organisms [ 174 ].…”
Section: Tools For the Study Of Host-pathogen Interactionsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that the microbiota may play a critical role in the immune response of organisms [ 174 ]. The “holobiome” approach on the study of fish host-pathogen interactions i.e., between the fish host, its microbiome, the pathogen, and other environmental microorganisms, has been pointed as a critical aspect for further development of rational strategies aiming at fish disease prevention and resistance [ 172 ]. Moreover, this holistic knowledge of fish host-pathogen interactions could contribute to promote sustainability in aquaculture, by reducing the use of antibiotics, responsible for a negative environmental impact of this industry [ 172 ].…”
Section: Tools For the Study Of Host-pathogen Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One evident expression of this interaction is that Artemia gets energy grazing on bacteria [58][59][60], which also provide enzymes to digest the algae and yeasts that are also Artemia food items. Additionally, environmental bacteria colonize and establish in the Artemia gut conforming the microbiota, which is known to provide multiple functional benefits to the host such as protection against pathogens, energy balance, immunological enhancement, and behavior [61]. Thus, imbalances (i.e., reduced diversity) in the microbiota composition due to environmental or other factors such as pathogens seriously affect the performance of the host in a given environment.…”
Section: The Artemia-bacteria Relationshipmentioning
confidence: 99%